Integrating physiology into the first two years of a new osteopathic medical school curriculum - Slater, Natalie F.; Nizamutdinova, Irina; Jacobs, Blaine A.; Slater, Robert T.; Bradley, Jessica M. (Frontiers in Physiology, 2023)
The integrated curriculum is a hot topic in curriculum reform in undergraduate medical education; however, there are varying definitions of the term, and resources guiding the integration of specific disciplines throughout the first two years of undergraduate medical education in a learner-centered curriculum are limited. Our first class matriculated into our osteopathic medical school in 2017, and since then we have developed and implemented a learner-centered, integrated curriculum that begins on day one for our learners. This paper will discuss our experience with the development and implementation of the University of the Incarnate Word School of Osteopathic Medicine (UIWSOM) curriculum with specific emphasis on how we incorporate physiology into it. This is a provisional file, not the final typeset article 2015), or lifestyle medicine (Phillips 2015), into already developed curricula or courses. While this may be beneficial for established medical institutions, this does not provide guidance to those newer allopathic and osteopathic medical schools that are starting from scratch. Since the first class matriculated into the Doctor of Osteopathic Medicine (DO) program at our osteopathic medical school in 2017, we have been able to design and implement our curriculum from the ground-up.In this paper, we will outline the learner-centered, integrated curricular structure at the University of the Incarnate Word School of Osteopathic Medicine (UIWSOM), describe the major philosophies underpinning our curriculum, explain how physiology is integrated with clinical and other basic sciences throughout the first two years, and discuss our experience with this endeavor, including challenges faced and future goals.